Implementasi Kegiatan Keagamaan dalam Meningkatkan Kualitas Akhlak Siswa di SMK IPTEK Weru Sukoharjo Tahun Ajaran 2018/2019 - Oktaveria Lilafi Nur Afidah (Academica : Journal of Multidisciplinary Studies, 2018)
AbstractIn Islam the barometer of one's level of faith is morals. Therefore, with the existence of religious activities, it will affect one's morals. The phenomenon of moral degradation seems to be rife among students. So there is a need for immediate handling, one of which is from the school. Schools can take policies that shape the character of moral and character students. The study examines the implementation of religious activities in improving the moral quality of students at Weru Sukoharjo Vocational School Science and Technology. This research uses a qualitative method with a descriptive approach. The results of the study are known that, Weru Sukoharjo Vocational School Science and Technology is one of the Vocational Schools in Sukoharjo Regency which is not Islamic based but implements various religious activities. Religious activities are divided into two types, namely activities outside of learning, such as simultaneous prayer, tilawatil quran, and Islamic studies, as well as activities in learning, such as tahsin and tahfidzul quran.Keywords: Religious activities, morals